Textos de divulgação científica com enfoque ciência, tecnologia, sociedade e ambiente na formação de professores de Química da educação básica - SOUSA, Bárbara Lethicya Silva (2019)
The scientific and technological advances, over the years, provide transformations to society and in this scenario, the school undergoes adjustments, which include the insertion of resources, techniques and methodologies as support to teaching and teaching practice. Considering the new educational trends, the concepts related to the Science, Technology, Society and Environment - CTSA movement and the Scientific Dissemination Texts (TDC), as current and diversified materials, we investigate in this work the potentialities of the TDC published in the section On magazine Ciência Hoje, from 2005 to 2018, for the insertion of CTSA in the teaching of Chemistry. Santos, Vilches and Brito (2016a), Santos, Vilches and Brito (2016b), 22 terms were adapted and used as CTS, CTSA and Sustainability approach lines. In the total of 840 articles analyzed 27% were selected and characterized. The results indicate for the area of Chemistry 67.5% attributions, Frontiers 18.73% with emphasis in the areas of Biology and Physics, Transverse Themes 27.89% with emphasis on ethics, health and environment. Regarding the lines of approaches CTS, CTSA and Sustainability, the texts were classified as the frequency of approach, having a 40% total for measures to solve problems and sustainable development. The specific subjects of the Chemistry curriculum were characterized in the areas of General Chemistry, Physical Chemistry and Organic Chemistry, with subjects such as study of the elements of the periodic table, acids and bases, electrolysis, organic functions, among others. Given the data obtained and considering the difficulties in the use of scientific dissemination materials (CTSA) and CTSA in teaching, we suggest a workshop as a didactic proposal, for the insertion of scientific dissemination materials (DC) with a CTSA focus in the teaching of Chemistry.